2009
DOI: 10.1016/j.mce.2008.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of type 2 diabetes

Abstract: Compared to the successful probing of genetic causes of monogenic disorders, dissecting the genetics of complex polygenic diseases has until recently been a fairly slow and cumbersome process. With the introduction of whole genome wide association studies (WGAS) the situation dramatically changed in 2007. The results from several recent WGAS on type 2 diabetes (T2D) and obesity have identified at least eighteen genes consistently associated with T2D. Many of the genes implicate pancreatic beta-cell function in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
114
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(116 citation statements)
references
References 80 publications
1
114
0
1
Order By: Relevance
“…As the FTO gene appears to increase diabetes risk mainly via obesity [20], no gene accounting for the observed r g between BMI and type 2 diabetes exists at present. Of the genes found for BMI, a significant proportion act through the central nervous system [4,5], whereas most diabetes genes implicate pancreatic beta cell function or insulin resistance [3]. In other words, despite the strong association between diabetes risk and obesity, only part of this association is explained by genetic similarity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the FTO gene appears to increase diabetes risk mainly via obesity [20], no gene accounting for the observed r g between BMI and type 2 diabetes exists at present. Of the genes found for BMI, a significant proportion act through the central nervous system [4,5], whereas most diabetes genes implicate pancreatic beta cell function or insulin resistance [3]. In other words, despite the strong association between diabetes risk and obesity, only part of this association is explained by genetic similarity.…”
Section: Discussionmentioning
confidence: 99%
“…The results from several recent genome-wide association studies have identified at least 18 genes consistently associated with type 2 diabetes [3]. After the initial discovery of FTO and MC4R genes, 15 new loci have so far been found for BMI [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recently years, genomewide association studies have identified various susceptibility genetic loci associated with T2DM in several ethnic populations (Hinney et al, 2010;Ridderstråle and Groop, 2009;McCarthy, 2010). Among the implicated genes include fat mass and obesity associated (FTO) Frayling et al, 2007), melanocortin 4 receptor (MC4R) (Chambers et al, 2008;Loos et al, 2008), solute carrier family 30 member 8 (SLC30A8) (Scott et al, 2007;Sladek et al, 2007;Zeggini et al, 2007), and potassium voltage-gated channel, KQT-like subfamily, member 1 (KCNQ1) (Unoki et al, 2008;Yasuda et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The recent advent of the genome-wide association studies of type 2 diabetes and its associated traits has proved to be a tremendous breakthrough in diabetes and metabolic research [1,2]. These studies have produced lists of genes, many of which were not suspected to be associated with the disease, to which the research field now needs to shift its attention.…”
Section: Introductionmentioning
confidence: 99%